1999
DOI: 10.1159/000006593
|View full text |Cite
|
Sign up to set email alerts
|

Posthatching Development of Spinal Motoneurons in the Angelfish <i>Pterophyllum scalare</i>

Abstract: We investigated the posthatching developmental sequence of spinal motoneurons innervating the axial muscles in the teleost angelfish, Pterophyllum scalare, by means of retrograde labeling with horseradish peroxidase. Two discrete types of spinal motoneurons, primary-type motoneurons and secondary motoneurons were labeled in a temporally different sequence during the course of larval development. These two types of motoneurons were morphologically distinguishable from one other. Primary-type motoneurons are gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(36 reference statements)
2
6
0
Order By: Relevance
“…The morphology and the location of the spinal motoneurons retrogradely labeled with HRP from the axial muscles in the larvae in the present experiment were consistent with the findings by Yoshida et al (1999). In addition, we found that the paired motoneurons tended to be labeled more intensely different posthatching stages including day 1 (6 and 18 hr after hatching), day 2, day 3, day 6, day 10, day 20 and adult, were examined electron microscopically.…”
Section: Hrp Labeling and Em Observation Of Motoneuronssupporting
confidence: 91%
See 4 more Smart Citations
“…The morphology and the location of the spinal motoneurons retrogradely labeled with HRP from the axial muscles in the larvae in the present experiment were consistent with the findings by Yoshida et al (1999). In addition, we found that the paired motoneurons tended to be labeled more intensely different posthatching stages including day 1 (6 and 18 hr after hatching), day 2, day 3, day 6, day 10, day 20 and adult, were examined electron microscopically.…”
Section: Hrp Labeling and Em Observation Of Motoneuronssupporting
confidence: 91%
“…To identify the ventral root containing the spinal motoneurons innervating the trunk muscles in the larvae at day 6 or younger stages, we retrogradely labeled the motoneurons with HRP according to the method of Yoshida et al (1999). After visualization of the HRP with DAB, the preparation was dehydrated and embedded in Quetol-812 resin.…”
Section: Retrograde Labeling Of Spinal Motoneurons With Hrpmentioning
confidence: 99%
See 3 more Smart Citations